Initial Public Offering (Ipo) Returns And Post-Listing Liquidity Effect Of Ownership Structure And Divergence Of Investors Opinion In The Malaysian Market - Ramlee, Roslily (2013)
Prior studies on the relationship between Initial Public Offering (IPO) returns and liquidity are mostly for the developed markets. The disperse ownership in the corporations and more well informed investors support their findings. On the other hand, the nature and behaviour of emerging stock markets such as Malaysia differ from the developed markets. The concentrated ownership partly due to government ownership, the behaviour of market participants and market policies could provide different views on the relation between liquidity and return. Given the difference in the environment, it is the objective of this study to reduce the existing gap by examining this relationship from the emerging market perspective. Using 299 samples of stocks listed on Bursa Malaysia from 1998 to 2008, the nature of relationship between (PO returns and liquidity is examined. Additionally, the effects of firm's ownership structure, government ownership and the divergence in investor's opinion on the return and liquidity relationship are examined.